2010
DOI: 10.1158/0008-5472.can-09-3565
|View full text |Cite
|
Sign up to set email alerts
|

Blueberry Phytochemicals Inhibit Growth and Metastatic Potential of MDA-MB-231 Breast Cancer Cells through Modulation of the Phosphatidylinositol 3-Kinase Pathway

Abstract: Dietary phytochemicals are known to exhibit a variety of anticarcinogenic properties. This study investigated the chemopreventive activity of blueberry extract in triple-negative breast cancer cell lines in vitro and in vivo. Blueberry decreased cell proliferation in HCC38, HCC1937, and MDA-MB-231 cells with no effect on the nontumorigenic MCF-10A cell line. Decreased metastatic potential of MDA-MB-231 cells by blueberry was shown through inhibition of cell motility using wound-healing assays and migration thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
128
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(150 citation statements)
references
References 49 publications
13
128
1
4
Order By: Relevance
“…These findings are consistent with earlier studies. Adams et al found that blueberry extracts, which were rich in ellagic acid, could modulate the PI3K/AKT/NF kappa B pathway and inhibit the growth and metastasis of MDA-MB-231 breast cancer cells (Adams et al, 2010). Li et al reported that ellagic acid induced G0/G1 cell cycle arrest and apoptosis in bladder cancer T24 cells .…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with earlier studies. Adams et al found that blueberry extracts, which were rich in ellagic acid, could modulate the PI3K/AKT/NF kappa B pathway and inhibit the growth and metastasis of MDA-MB-231 breast cancer cells (Adams et al, 2010). Li et al reported that ellagic acid induced G0/G1 cell cycle arrest and apoptosis in bladder cancer T24 cells .…”
Section: Discussionmentioning
confidence: 99%
“…There have been a plethora of reports in the scientific literature documenting the chemopreventive potential of phytochemicals such as Lupulone, Hesperidin and blueberry phytochemicals in various cancer cell lines like those from tumors in the colon and the breast (Park et al, 2008;Lamy et al, 2009;Adams et al, 2010). Further, studies have been done to demonstrate that the common unifying theme involves the activation of caspase-3, despite differences in the relative involvement of the upstream molecular players in the extrinsic and intrinsic pathways of apoptosis with respect to Curcumin treatment (Gao et al, 2005;Takai et al, 2012).…”
Section: Cytotoxicity Apoptosis Induction and Anti-metastatic Potentmentioning
confidence: 99%
“…Phytochemicals in blueberries have been shown to decrease the secretion of urokinase-type plasminogen activator (uPA) and increase the secretion of plasminogen activator inhibitor (PAI), both of which are cell-signaling proteins that inhibit tumor cell proliferation and metastatic potential in breast cancer cells (Adams et al, 2010). Anthocyanin, the flavonoid responsible for the pigmentation in blueberries, has both antioxidant and anti-cancer properties (Seeram, Yanjun, & Muraleedharan, 2003).…”
Section: Introductionmentioning
confidence: 99%